Is there a bubble in the art market? - Roman Kräussl; Thorsten Lehnert; Nicolas Martelin (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
The record-breaking prices observed in the art market over the last three years raise the question of whether we are experiencing a speculative bubble. Given the difficulty to determine the fundamental value of artworks, we apply a right-tailed unit root test with forward recursive regressions (SADF test) to detect explosive behaviors directly in the time series of four different art market segments ("Impressionist and Modern", "Post-war and Contemporary", "American", and "Latin American") for the period from 1970 to 2013. We identify two historical speculative bubbles and find an explosive movement in today's "Post-war and Contemporary" and "American" fine art market segments.
urn:nbn:de:hebis:30:3-355818
Keywords: G12; G14; Z11; 330; Art market; Alternative investments; Speculative bubbles; Explosive behavior